Synthetic spatial patterning in bacteria: advances based on novel diffusible signals. Issue 6 (29th November 2021) - Oliver Huidobro, Martina; Tica, Jure; Wachter, Georg K. A.; Isalan, Mark
Summary: Engineering multicellular patterning may help in the understanding of some fundamental laws of pattern formation and thus may contribute to the field of developmental biology. Furthermore, advanced spatial control over gene expression may revolutionize fields such as medicine, through organoid or tissue engineering. To date, foundational advances in spatial synthetic biology have often been made in prokaryotes, using artificial gene circuits. In this review, engineered patterns are classified into four levels of increasing complexity, ranging from spatial systems with no diffusible signals to systems with complex multi‐diffusor interactions. This classification highlights how the field was held back by a lack of diffusible components. Consequently, we provide a summary of both previously characterized and some new potential candidate small‐molecule signals that can regulate gene expression in Escherichia coli . These diffusive signals will help synthetic biologists to successfully engineer increasingly intricate, robust and tuneable spatial structures. Abstract : Engineering multicellular patterning may help in the understanding of some fundamental laws of pattern formation. In this review, engineered patterns are classified into four levels of increasing complexity, ranging from spatial systems with no diffusible signals to systems with complex multi‐diffusor interactions. We provide a summary of candidate small molecule signals to help synthetic biologists to engineer tuneable spatial structures.